The Relative Proportion of Preterm Births Complicated by Premature Rupture of Membranes in Multifetal Gestations: A Population-Based Study - Pakrashi, Tarita; Defranco, Emily A. (American Journal of Perinatology, 2013)
Objective To compare the relative contribution of premature rupture of membranes (PROM) to preterm births in singleton compared with multifetal gestations.Study Design A population-based retrospective cohort study of 291,782 nonanomalous live births in the state of Ohio from January 1, 2006, to December 31, 2007, identified through birth certificate data. Frequency of PROM was compared between singleton and multifetal gestations and then stratified by gestational age at birth. Multivariate regression analysis estimated the risk of PROM by plurality in each gestational age group, accounting for influential risk factors.Results The frequency of PROM increased with increasing plurality of gestation. The relative proportion of preterm birth <37 weeks complicated by PROM increased with gestational plurality 13.2% singletons, 16.8% twins, 20.0% triplets, 19.6% quadruplets, and 100% for higher-order multiples (p < 0.001). The frequency of PROM increased with earlier gestational age at birth, regardless of plurality. The increased risk of PROM in multifetal gestation persisted even after adjustment for influential concomitant risk factors.Conclusion The proportion of preterm birth attributable to PROM increases by plurality of gestation, with its most significant contribution in higher-order multiples and at earliest gestational ages when outcomes are the poorest.
Keywords: PROM; preterm/premature birth; multifetal gestation; preterm rupture of membranes; preterm labor